COMPUTER-BASED SYSTEMS OF PHYSICAL EXPERIMENT IN INDEPENDENT WORK OF STUDENTS OF TECHNICAL UNIVERSITY - Slipukhina, Iryna; Mieniailov, Serhiy; Bovtruk, Alla (Proceedings of National Aviation University, 2016)
Purpose: The self-study activity of students is an important form of educational process under the conditions of rapid changes of technologies. Ability and readiness of future engineers for independent education is one of their key competences. Investigation of modern methods of planning, organization and control of independent cognitive activity of students while studying physics as effective means of complex forming of their professional qualities is the object of the research. Methods: We analyse the curricula of some engineering specialities in leading technical universities, existent methods and forms of organization of students’ self-study, and own pedagogical experience. Results: Based on the theoretical analysis of existing methods of students’ self-study, it was found that a systematizing factor of appropriate educational technology is the problem focused cognitive tasks. They have to be implemented by application of the modern technological devices integrated with a computer-based experiment. We define the aim of individual or group laboratory works; the necessary theoretical and practical knowledge and skills of students are rationalized; timing and form of presentation of the results are clarified after individual and group consulting. The details of preparatory, searching-organizational, operational, and control stages in organization of students’ self-study with the use of computer oriented physical experiment are specified, these details differ depending on the didactic purpose, form of organization and students’ individuality. Discussion: The research theoretical aspect confirms the determining role of subject-subject cooperation in forming of competences of independent learning of the future engineers. Basic practical achievements of the research consist of improving methods of using of digital learning systems, creation of textbooks that promote consultative and guiding role for the educational process, working-out of the electronic documents and lab reports